The Correlation Between Close Contact and Environment with TB Incidence - Intan Dwi Putri Permatawati; Marfuah; Alwin Widhiyanto (KHD Production, 2025)
Tuberculosis (TB) remains a significant public health issue in Indonesia. This infectious disease burdens the affected individuals and impacts their families and the wider community. This study aims to determine the relationship between close contact and environmental factors with the incidence of Tuberculosis (TB) in the working area of Puskesmas Tekung. This quantitative research employs an analytical correlation design. The sample consists of 30 respondents who received services at the general clinic of Puskesmas Tekung, selected using accidental sampling techniques. The results show that most respondents (21 or 70%) did not have close contact with TB patients. Additionally, most respondents (22 or 73.3%) lived in a healthy environment. TB-negative results were found in 19 respondents (63.3%). Bivariate analysis using the Chi-Square test revealed a significant relationship between close contact and the incidence of TB with a p-value of 0.000. A similar significant relationship was found between environmental factors and TB incidence, where respondents living in a healthy environment were less likely to contract TB (p=0.000). The proposed solution is to enhance educational programs and public outreach about maintaining distance from TB patients and creating a healthy environment. This can be achieved through seminars, educational material distribution, and health campaigns at the village level. Additionally, it is crucial to promote clean living habits, including mask usage and proper coughing etiquette, and to strengthen environmental sanitation efforts to reduce the risk of TB transmission.